Handbook of research on industrial applications for improved supply chain performance - García-Alcaraz, Jorge Luis; Jamil, George Leal, 1959-; Avelar-Sosa, Liliana, 1977-; Briones Peãlver, Antonio Juan (IGI Global, 2019)
"This book examines techniques, tools, and methodologies being implemented to improve supply chain performance to generate competitive advantage in companies"--